Positioning and Utilizing Sensors on a 3-D Terrain Part I-Theory and Modeling - (:unkn) unknown (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2011)
Positioning multiple sensors for acquisition of a given environment is one of the fundamental research areas in various fields, such as military scouting, computer vision, and robotics. In this paper, we propose a new model for the problem of sensor deployment. Deploying and configuring a set of given sensors on a synthetically generated 3-D terrain have multiple objectives on conflicting attributes: maximizing the visibility of the given terrain, maximizing the stealth of the sensors, and minimizing the cost of the sensors used. Since they are utility-independent, these complementary and conflicting objectives are modeled by a multiplicative total utility function, based on multiattribute utility theory. The total utility function proposed in this paper can also be adapted for various military scouting missions with different characteristics.
Keywords: Multiattribute utility (MAU) theory; multiobjective optimization; sensor planning; viewpoints; ROBOT VISION; NETWORKS; OCCLUSION; COVERAGE